OPTIMASI KONSENTRASI ENZIM AMILOGLUKOSIDASE DAN Saccharomyces cerevisiae DALAM PEMBUATAN BIOETANOL DARI UBI JALAR (Ipomoea batatas L) VARIETAS DAYA DENGAN PROSES SAKARIFIKASI FERMENTASI SIMULTAN (SFS) - Anita, Ni Wayan; Admadi H, Bambang; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 2 (2015): Juni)
The purpose of this study was to 1). Determine the effect of concentration enzyme amiloglukosidase and Saccharomyces cerevisiae to concentration ethanol, total sugars end, efficiency of product formation and yield 2). Determine the concentration of enzymes amiloglukosidase and Saccharomyces cerevisiae the best in the Simultaneous Saccharification Fermentation (SSF). The fermentation process is implemented using a factorial randomized block design with concentration factor of amiloglukosidase enzyme (2000 U / L, 2500 U / L, 3000 U / L) and concentration factor of Saccharomyces cerevisiae (5, 10 and 15% (w / v)). Stage of research include: the process of enzymatic liquefaction, simultaneous saccharification fermentation and distillation. The results showed that the interaction between the enzyme amiloglukosidase and Saccharomyces cerevisiae significant effect on the observed parameters, the concentration enzyme amiloglukosidase 2500 U / L and Saccharomyces cerevisiae 10% (w / v) produced ethanol content of 6.61 % , the yield of 17.58 % , total sugar end 12.44 %, and product formation by substrate 52.41 % .
Keywords: 40,